Teaching Competencies Necessary for Teachers in Colleges of Education - Sabry, Daoud A. (Humanities Journal of University of Zakho, 2013)
The study seeks to detect the availability of teaching competencies in students Almtbakan, by answering what comes: - Identify the necessary teaching competencies among students / Almtbakan from the point of view of Altdresen supervisors applications according to the areas of planning for the lesson, implementation, and evaluation. - Appropriate proposals for the development of the development of teaching competencies for students Almtbakan from the point of view of Altdresen supervisors applications? Sample consisted of (40) pedagogy and teaching have been selected in the manner intentionality who is assigned to them, supervise students was a Almtbakan (24) pedagogy (16) teaching. The search tool consisted of (32) paragraph and in front of each paragraph three alternatives are (often available, sometimes available, rarely available). After that make sure the researcher to check sincerity tool and persistence, the researcher distributed the questionnaire to the sample core of Altdresen and Altdriciat and asked them to answer paragraphs resolution, and this is done in the course of the field visit of students applied to the teacher training and secondary schools during the period of application, located in the second semester . It was evident from the results that the teaching competencies necessary for students Almtbakan, were counted in three key areas, planning, implementation, and evaluation, and for each of the three areas of a number of sub-caliber faculty. The efficiencies obtained the calendar on the first place, either efficiencies and implementation planning third place and it is clear that teaching competencies for students moderately Almtbakan. In light of the results of research and his questions the researcher concluded that the necessary teaching competencies necessary for students Almtbakan, which must be used as a criterion for student applied was reduced to three main areas (planning for the lesson, and implementation of the lesson, and Calendar) 0 In light of these results, the researcher recommended to benefit from a list of teaching competencies that this study’s findings in the area of ​​evaluating the performance of students applied to the process of educational supervision by moderators.